THE INCREASE OF OMEGA-3 BY FEEDING BALI CATTLE WITH SUPPLEMENTATION LEMURU FISH OIL IN MOLAMIX CONCENTRATE - Sriyani, N.L.P.; Putra, S.; Saka, IK.; Gaga Partama, I.B. (E-Journal of Animal Science Udayana University; Vol 3, No 1, Tahun 2014)
This study was carried out to increase the content of Omega-3 (EPA and DHA) on beef by feeding bali cattle with supplemented lemuru fish oil in Molamix concentration. A Randomized Complete Block Design was applied consists of 3 treatment diets and 4 weight groups as replication. There were tweleve Bali cattle used at range weigh of 248-277 kg. The cattle randomly allocated into 3 treatments fed with elephant grass + concentrate without fish oil supplementation as control (RKMBI 10 ); elephant grass + concentrate with lemuru fish oil supplementation 5% (RKMBI 5 ); and lemuru fish oil supplementation 10% (RKMBI 10 ). The study showed that lemuru fish oil supplementation decreased dry matter consumption (BK) in accordance with the increase of concentration energy content. Fish oil supplementation produces ALA in beef fat RKMBI 0 at 0.18%, RKMBI 5 at 0.20% and RKMBI 10 at 0.14 % which was not significantly different. While the EPA content in beef fat RKMBI 5 at 0.07% higher than the beef meat RKMBI 0 at 0.05%, and RKMBI 10 at 0.04 %. RKMBI5 beef content of DHA. In contrary, 0.06 % was not found on RKMBI 0 and RKMBI 10 beef. The amount of omega-3 content in each 100 g of RKMBI 5 at 1.16 mg and RKMBI 10 at 1.75 mg significantly (P<0.05) higher than RKMBI 0 at 0.60 mg. It can be concluded that fish oil supplementation in molamix lemuru concentrate decreased ration palatability which lead to decrease dry matter consumption. However, fish oil supplementation significantly increased the amount content of omega-3/100g on bali cattle.
Keywords: lemuru oil , meat of omega-3, bali catle, feed intake